2011
DOI: 10.1021/nl201823u
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional High-Density Hierarchical Nanowire Architecture for High-Performance Photoelectrochemical Electrodes

Abstract: Three-dimensional (3D) nanowire (NW) networks are promising for designing high-performance photoelectrochemical (PEC) electrodes owing to their long optical path for efficient light absorption, high-quality one-dimensional conducting channels for rapid electron-hole separation and charge transportation, as well as high surface areas for fast interfacial charge transfer and electrochemical reactions. By growing titanium dioxide (TiO(2)) nanorods (NRs) uniformly on dense Si NW array backbones, we demonstrated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
233
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(239 citation statements)
references
References 36 publications
6
233
0
Order By: Relevance
“…To date, a variety of inorganic heterojunction architectures have been developed to enhance the efficiency of photoelectrochemical water splitting cell. [22][23][24][25][26][27][28][29][30] In our study, we adapted this long-established strategy to enhance the photocatalytic activity of hydrothermally grown TiO 2 nanorod array. As a coupling material, we chose ZnO because its conduction band-edge is positioned at more negative potential in comparison with that of TiO 2 , thus being suitable for building the type-II band alignment (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…To date, a variety of inorganic heterojunction architectures have been developed to enhance the efficiency of photoelectrochemical water splitting cell. [22][23][24][25][26][27][28][29][30] In our study, we adapted this long-established strategy to enhance the photocatalytic activity of hydrothermally grown TiO 2 nanorod array. As a coupling material, we chose ZnO because its conduction band-edge is positioned at more negative potential in comparison with that of TiO 2 , thus being suitable for building the type-II band alignment (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Shi et al demonstrated that the novel 3-D high-density heterogeneous NW architecture of Si/TiO 2 could enhance PEC efficiency. 29 A 3-D NW architecture consisting of 20 μm long wet-etched Si NWs and dense TiO 2 NRs yielded a PEC efficiency of 2·1%, which was three times higher than that of Si NWs/TiO 2 core-shell film ( Figure 16). The author also proved that the efficiency could be further improved by optimising the number of overcoating cycles and the length/density of NW backbones.…”
Section: Branched Nanostructures For Photoelectrochemical Water Splitmentioning
confidence: 99%
“…Branched nanostructures for photoelectrochemical water splitting Mao reported by the same group 29 showed high hydrogen production efficiency, they require high biasing potential to drive water splitting. In this regard, the branched CuO/ZnO NWs may be more promising because they are photoactive at low biasing potentials.…”
Section: Nanomaterials and Energy Volume 3 Issue Nme4mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Accordingly, one-dimensional (1-D) nanostructures such as nanowires, nanotubes, and nanorods are advantageous over planar geometries because these structures permit considerable light absorption depths, enhanced charge separation by providing high electrode/ electrolyte interface areas, and a reduction in the charge carrier transport distance to the electrolyte, which increases quantum efficiency. 9 In addition, some dopants such as nitrogen (N), carbon (C), and hydrogen (H) serve as electron donors to contribute to light absorption in the visible region and increase the electrical conductivity of the film. 10 In particular, the valence band edge of nonmetal (N, C)-incorporated TiO 2 is upshifted by forming impurity states above the valence band or hybridizing with O 2p states to extend the absorption spectrum toward the visible light region.…”
Section: Introductionmentioning
confidence: 99%